Sodium and Fat Consumption Patterns and Family History Among Hypertension Patiens in Banjarmasin City - Afifa amelia, Putri; Aprianti; Dwi Andrestian, Meilla (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2025)
Hypertension is a major cause of death among adults in Indonesia. In 2023, the highest cases were reported at Terminal Community Health Center (12,744 cases) and the lowest at Pelambuan (3,648 cases). This study compared sodium and fat consumption patterns and family history among hypertensive patients aged 45–59 years, and identified the dominant factor influencing hypertension. A cross-sectional design was applied with 109 respondents selected through proportional and accidental sampling. Data were collected using a semi-FFQ, family history questionnaire, and blood pressure measurements. Data analysis used Mann-Whitney tests and logistic regression. Results showed significant differences in sodium intake (p=0.025), fat intake (p=0.000), and family history (p=0.017) between the two centers. Multivariate analysis revealed that family history was the dominant factor related to hypertension. In conclusion, family history plays a key role in hypertension risk, supported by unhealthy dietary patterns. Practical implications highlight the need for continuous nutrition education and family-based interventions, especially for those with a family history of hypertension. Longitudinal research is recommended to confirm these findings.